Microbial fuel cells (MFCS) for sustainable energy production: an Islamic approach - Zainan Nazri, Nurul Jannah; Samsudin, Sofiah; Jani, Mohd. Shah; Nik Mohd Kamal, Nik Nur Madihah (IIUM Press, International Islamic University Malaysia, 2018)
Introduction Modern science must be studied in its philosophical foundations from the Islamic point of view. This is to reveal for Muslims what are the value system and philosophical assumptions of the nature and the universe. It should be based on a concrete value system and philosophical assumptions which is ultimately comes from God and are not merely human forms of knowledge (Iqbal, 2009). On another note, the framework for action of the World Conference on Science that was held in Budapest, 1999, also stated that ethics and the responsibility of science should be an integral part of the education and training of all scientists (UNESCO, 2006)